Triathlon-related musculoskeletal injuries: a study on a Portuguese Triathlon Championship - Minghelli, B.; Jesus, C.; Martins, I.; Jesu, J. (Revista da Associação Médica Brasileira, 2020)
BACKGROUND: A triathlon consists of 3 modalities: swimming, cycling and running. Its higher training frequency, the environmental factors and extrinsic factors (technique and equipment) may lead to injuries. This study aimed to determine injury epidemiology in triathletes, as well as their type, location, mechanism of injury, and risk factors.METHODS: The sample was constituted of 174 triathletes who participated in the Triathlon Club Portuguese Championship, being 131 (75.3%) male, aged 18 to 70 years old (36.09±11.03). The measurement instrument was a questionnaire concerning the characterization of the population and aspects related to the modality and injuries.RESULTS: One hundred and twenty (69%) athletes reported one injury since the beginning of their practice, and 95 (54.6%) had an injury in the previous year, with a total of 130 injuries. There were 2.39 injuries per 1,000 hours of triathlon training. The most common injuries were muscle contusion (31.5%) and inflammatory injuries (19.2%), located in the knee (22.3%) and the leg (18.5%). Overtrain-ing (43.1%) was the mechanism that led to the highest occurrence of injuries. Fourteen (10.8%) injuries occurred during swimming, 23 (17.7%) during cycling, and 93 (71.5%) during running. No statistical significance was observed between the risk factors analyzed and the occurrence of injuries.CONCLUSIONS: Triathlon practice is associated with a high prevalence of injuries, being contusions, knee, and overtraining the most common type, location, and mechanism of injury respectively. It is necessary to create injury prevention strategies, including specific training and suitable materials for use by athletes.